DEVELOPING ENGLISH READING TEACHING MATERIALS WITH ISLAMIC MATERIALS AND VALUES FOR STUDENTS AT ISLAMIC BOARDING SCHOOLS BASED ON CONTEXTUAL TEACHING LEARNING - Dedi Efrizal (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2022)
Most of students in class XI at Darussalam Kepahiang Modern Islamic Boarding School, Bengkulu, encountered many problems in reading skill. The main problem was there were not appropriate teaching English reading materials yet that give big portion and opportunity for the students to read actively based on their contextual or daily experiences in order to support teaching and learning process of English reading in Islamic boarding school. The objective of this research was developing a set of supplementary teaching English reading With Islamic Materials and Values for the students based on Contextual Teaching and Learning. This research used Research and Development design with the procedures: conducting need assessment, developing supplementary materials, conducting expert validation, revising the materials, trying out the materials, and revising the materials. The researcher collected the data by using questionnaires, interviews, analyzing the syllabus, and field notes. The product of this research is four units of supplementary teaching English reading class XI at Pondok Pesantren Modern Darussalam Kepahiang, Bengkulu, Indonesia